Identifikasi faktor penyebab kejadian unsafe action dan unsafe condition pada pekerja lapangan - Syalfi Intan Riyani; Budi Aswin; Herwansyah Herwansyah; Usi Lanita (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Workplace accidents remain a major concern in the energy sector. Unsafe acts and conditions are the leading cause of accidents, with over 85% of incidents related to unsafe behavior. PT. PLN Indonesia Power's Payo Selincah Jambi Power Plant Unit, with 144 workers, recorded 99 workplace accidents in 2019–2021.Purpose: To identify factors underlying unsafe acts and unsafe conditions among field workers.Method: Qualitative research using a case study approach. Six informants were purposively selected: the unit manager, the OHS team leader, the head of operations, the head of maintenance, and two field workers. Data were collected through in-depth interviews, observation, and documentation, then analyzed thematically.Results: Two main themes were identified: human behavioral factors, low PPE compliance due to unfamiliarity and discomfort, "cat and mouse" behavior toward supervisors, and neglect of procedures during emergencies. Environmental factors are generally well managed through routine housekeeping, waste management, and annual PPE replacement, but outdoor work in extreme weather conditions remains risky. Conclusion: The main challenge lies in the genuine internalization of a safety culture. It is recommended to review the ergonomics of personal protective equipment (PPE), strengthen the reward-punishment system, implement emergency simulation training, and formalize safe work practices across all units. Keywords: Field Workers; Occupational Safety And Health; Power Plants; Unsafe Action; Unsafe Condition.